Towards a Better Future for Canadians with Bipolar Disorder: Principles and Implementation of a Community-Based Participatory Research Model (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2015)
The Collaborative RESearch Team to study psychosocial factors in bipolar disorder (CREST.BD) is a multidisciplinary network dedicated to advancing science and practice around psychosocial issues associated with bipolar disorder (BD), improving the care and wellness of people living with bipolar disorder, and strengthening services and supports for these individuals. CREST.BD specializes in community-based participatory research, in which research is conducted as a partnership between researchers and community members. This article describes the evolution of the CREST.BD network and CREST.BDâ€™s commitment to community-based participatory research in bipolar disorder research. Examples of CREST.BD projects using community-based participatory research to study stigma, quality of life, psychosocial interventions, and creativity in bipolar disorder are highlighted, and opportunities and challenges of engaging in community-based participatory research in bipolar disorder specifically and the mental health field more broadly are discussed. This article demonstrates how CBPR can be used to enhance the relevance of research practices and products through community engagement, and how community-based participatory research can enrich knowledge exchange and mobilization.Â